Geographical mapping of road traffic injuries in Lilongwe, Malawi. Issue 4 (April 2021) - Sundet, Mads; Mulima, Gift; Kajombo, Chifundo; Gjerde, Hallvard; Christophersen, Asbjørg S.; Madsen, Jan Erik; Young, Sven
Highlights: This study presents a novel method of mapping road traffic injuries by recording them on free software on a tablet in the Emergency room at admission. 1244 patients were included and 5 hotspots were identified. In these hotspots, 148 patients were injured during a time span of 90 days. Rural setting, age over 55, alcohol use before injury, high speed limit at the site of injury, not using seat belts and being a pedestrian or motorcyclist were significantly associated with a higher degree of severity. Abstract: Background: Road traffic injuries are a leading cause of death and disability, especially in low- and middle-income countries. Identifying injury hotspots are valuable for introducing preventive measures. This is usually accomplished by using police data, but these are often unreliable in low-income countries. This study aimed to identify hotspots for injuries by collecting geographical data in the emergency room. Methods: This was a cross-sectional study of adult road traffic injury patients presenting to the Casualty Department in the central hospital in Lilongwe, the capital of Malawi. An electronic tablet with downloaded maps and satellite photos was used to establish the exact location of the injuries. The geographical data were analyzed with geographic information software. Results: We included 1244 road traffic injured patients, of which 23.9% were car passengers or drivers, 18.6% were motorcyclists, 17.8% were pedestrians and 18.0% were cyclists or bicycle passengers. Heatmaps of the injuries identified 5 locations where the incidence of injuries was especially high, and 148 patients were injured in these hotspots during the 90 days of inclusion. Four of these hotspots were along the main road through the capital. Age over 55, rural setting, alcohol use before the injury, high speed limit at the site of injury and being a pedestrian or motorcyclist were significantly associated with a higher degree of injury severity. Around half of the patients that were injured in a four-wheeled vehicle did not use a seat belt, and these patients had a much higher risk of getting a more severe injury. Conclusion: We have identified specific locations with a high incidence of road traffic injuries in Lilongwe, Malawi, with a simple methodology and within a short time frame. The study demonstrates the feasibility of collecting geographical data at admission to hospital.